1986
DOI: 10.1073/pnas.83.3.792
|View full text |Cite
|
Sign up to set email alerts
|

Increased mRNA for low density lipoprotein receptor in livers of rabbits treated with 17 alpha-ethinyl estradiol.

Abstract: Pharmacologic doses of 17a-ethinyl estradiol are known to increase the number of low density lipoprotein (LDL) receptors in livers of rats, thereby producing a profound fall in plasma cholesterol levels. We now report that ethinyl estradiol exerts the same effect in livers of male and female rabbits and that the increase in receptor number is correlated with a 6-to 8-fold increase in the levels of receptor mRNA. Receptor protein was measured by ligand blotting, and mRNA levels were measured by a quantitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
2
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(69 citation statements)
references
References 29 publications
5
60
2
1
Order By: Relevance
“…It has been shown that induction of hepatic LDL-R activity is the major mechanism responsible for the hypocholesterolemic effects of estrogen (38,39). In rats, estrogen induces expression of hepatic LDL-R (40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that induction of hepatic LDL-R activity is the major mechanism responsible for the hypocholesterolemic effects of estrogen (38,39). In rats, estrogen induces expression of hepatic LDL-R (40).…”
Section: Discussionmentioning
confidence: 99%
“…Because estrogens also affect the production of lipoproteins, we also examined the regulation of apoAI and apoB production in both species to ascertain whether any rat/mouse differences in the responses of the LDL-receptor were also applicable to apoA1 and apoB. In rats, both 17u-ethinyl estradiol and 17p-estradiol produced an almost complete disappearance of all lipoproteins from plasma [5,11,121. However, in mice, estradiol produced 2-fold increases in plasma apoB while drops in HDL-cholesterol and apoAI levels were relatively small (Tables 1 and 2, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this possibility, several hypolipidemic agents, such as cholestyramine [10] and 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitors [1 1, 12], which induce LDL receptor expression, have been used to lower serum Lp(a), but most of these attempts have failed to demonstrate any reduction. The only exception is estrogen, a hormone which elevates LDL receptors and reduces LDL-cholesterol [13,14]. Very recently, we observed a marked reduction in serum Lp(a) in a patient with familial hypercholesterolemia (FH) following estrogen therapy for prostatic cancer [15].…”
Section: Lipoproteinmentioning
confidence: 95%
“…Although the exact mechanism of estrogen's action was unknown, we previously proposed [15] that enhanced Lp(a) removal via LDL receptors might be responsible for the reduction in serum Lp(a), because the reduction in serum Lp(a) occurred in parallel with that of LDL-cholesterol, and estrogen is known to cause a significant decrease in LDL by increasing LDL-receptor expression, and hence LDL uptake in the liver [13,14]. Certainly the LDL receptor is a possible candidate, but our recent observations [24] as well as those of others [10][11][12], indicate that intervention trials with hypolipidemic agents, such as cholestyramine and HMG CoA reductase inhibitors, which induce LDL-receptor expression, do not cause a reduction in serum Lp(a), while estrogen does.…”
Section: Statistical Analysis Serum Lp(a)mentioning
confidence: 99%